Controle da dor pós-operatória da artroplastia total do joelho: é necessário associar o bloqueio do nervo isquiático ao bloqueio do nervo femoral? - Zugliani, Affonso H. (2007)
BACKGROUND AND OBJECTIVES: Total knee arthroplasty (TKA) causes severe tissue trauma, leading to severe postoperative pain. Good postoperative analgesia is fundamental and one should consider that early mobilization of the joint is an important aspect to obtain good results. There is a controversy in the literature on the efficacy of isolated femoral nerve block. The objective of this study was to evaluate postoperative analgesia with the association of sciatic and femoral nerve block. METHODS: Seventeen patients undergoing TKA under spinal anesthesia were divided in two groups: A and B. In Group A (n = 9), femoral nerve block was performed, while in Group B (n = 8), femoral and sciatic nerve block were done. The blockades were done in the immediate postoperative period with 20 mL of 0.5% of ropivacaine. Pain was evaluated in the first 24 hours using the Visual Analog Scale and the verbal scale. The length of time between the nerve block and the first complaint of pain (M1) was also evaluated. RESULTS: The median of the duration of analgesia (M1) in Group A was 110 min, while in Group B it was 1285 min (p = 0.0001). There were no complications related to the technique used. CONCLUSIONS: Sciatic nerve block, when associated with femoral nerve block, under the conditions of the present study, improved significantly the quality of postoperative analgesia in TKA.